2023
DOI: 10.2196/37742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music on Attention-Deficit/Hyperactivity Disorder (ADHD) and Potential Application in Serious Video Games: Systematic Review

Abstract: Background Attention-deficit/hyperactivity disorder (ADHD) has a considerable impact on an individual’s daily life. Some difficulties with timing deficits may be associated with deficiencies in attention, reading, language skills, or executive function. Music therapy, either active (playing an instrument) or passive (listening to music) has demonstrated its efficacy in reducing symptomatology in many disorders. Video games may prove to be a useful assessment and treatment tool in compensating for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…Overall, the results suggested that the intervention effectively enhanced the resilience and improved the depressive symptoms, self‐esteem, and QoL of children from low‐income families. The findings are in line with the results of previous studies on the effects of music‐based interventions in terms of improving psychological outcomes (da Silva Santa et al., 2021 ; Martin‐Moratinos et al., 2023 ; Mayer‐Benarous et al., 2021 ). Previous music‐based interventions are mainly active or passive music therapy focusing on music listening or improvisation (da Silva Santa et al., 2021 ; Martin‐Moratinos et al., 2023 ) but not instrumental musical training.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, the results suggested that the intervention effectively enhanced the resilience and improved the depressive symptoms, self‐esteem, and QoL of children from low‐income families. The findings are in line with the results of previous studies on the effects of music‐based interventions in terms of improving psychological outcomes (da Silva Santa et al., 2021 ; Martin‐Moratinos et al., 2023 ; Mayer‐Benarous et al., 2021 ). Previous music‐based interventions are mainly active or passive music therapy focusing on music listening or improvisation (da Silva Santa et al., 2021 ; Martin‐Moratinos et al., 2023 ) but not instrumental musical training.…”
Section: Discussionsupporting
confidence: 91%
“…The findings are in line with the results of previous studies on the effects of music‐based interventions in terms of improving psychological outcomes (da Silva Santa et al., 2021 ; Martin‐Moratinos et al., 2023 ; Mayer‐Benarous et al., 2021 ). Previous music‐based interventions are mainly active or passive music therapy focusing on music listening or improvisation (da Silva Santa et al., 2021 ; Martin‐Moratinos et al., 2023 ) but not instrumental musical training. This is the first study using the group‐based instrumental musical training approach to improve the resilience and QoL of school‐aged children from low‐income families.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, a recent review indicated that listening to music can reduce symptoms of ADHD and improve timing perception and regulation [22], which are important aspects for the functionality and well-being of this population.…”
Section: Introductionmentioning
confidence: 99%
“…Serious games have been proposed for neurodevelopmental disorder interventions primarily due to their appeal, engagement, and effectiveness [11 ,12 ]. Meanwhile, music therapy [13 ], exercise therapy [14 ], and chess therapy [15 ,16 ], shown to be effective for managing ADHD symptoms in children, can achieve better therapeutic effects when combined with serious games. In June 2023, the International Standards Organization (ISO) released Digital Therapies (DTx, ISO/TR 11147), which are evidence-based therapeutic interventions driven by software to prevent, manage, or treat a medical disorder or disease.…”
Section: Introduction Backgroundmentioning
confidence: 99%